#TITLE_ALTERNATIVE# - NAMARA (NIM:15111036) Pembimbing : Dr. Heri Andreas, ST., MT., RIANDI
In real-time positioning, has known the Real Time Kinematic (RTK) and Real Time Precise Point Positioning (RTPPP). RTK systems using a single reference station generally only be used for the baseline distances up to about 1-15/20 km. RTPPP system used the duration to measure of a single point usually ranges from Ã‚Â±30 minutes. In this study conducted GPS observations Long Baseline RTK which uses a reference station at a distance of over 20 km with a solution float RTK and Quick Survey RTPPP the initialization process and the measurements are made in a short time which can be an alternative as a measurement solution GCP (Ground Control Point) for rectification of high resolution satellite imagery. The purpose of this research was to compare the ability of the the Long Baseline RTK and Quick Survey RTPPP methods by measuring GCP for rectification Quickbird image of Bandung in 2009 with a spatial resolution of 0.6 m. Satellite imagery is cut to fit the specified area of study. Based on the results of rectification can know the level of efficiency of the two methods in terms of duration and technical aspects of data acquisition. Through this research, the RMSE values of the two methods is greater than the spatial resolution QuickBird imagery. Results of Long Baseline RTK rectification method with RMSE values of 1.09 m and a Quick Survey method RTPPP with RMSE values of 1.11 m. This is caused some data that indicated ouliers, then repeat rectification without of outliers data and produces a RMSE values that is smaller than the resolution Quickbird imagery, Long Baseline RTK method with RMSE values of 0.59 m and a Quick Survey method RTPPP with RMSE values 0, 43 m.